A novel allele, HLA‐DRB1*12:60N, detected in a Taiwanese unrelated hematopoietic stem cell donor. (17th November 2016) - Yang, K. L.; Lin, P. Y.
Abstract : One nucleotide deletion at residue 157 of HLA‐DRB1*12:02:01 results in a new allele, HLA‐DRB1*12:60N.